Microsatellites to reveal genetic diversity and to distinguish four mangoes of Tegal District, Central Java, Indonesia - ANNUR HIDAYAT; ENNI SUWARSI RAHAYU; MUHAMMAD ABDULLAH; Amin Retnoningsih (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hidayat A, Rahayu ES, Abdullah M, Retnoningsih A. 2021. Microsatellites to reveal genetic diversity and to distinguish four mangoes of Tegal District, Central Java, Indonesia. Biodiversitas 22: 3467-3473. The Wirasangka mango is Tegal District’s flora of identity, which requires recognition, and its existence deserves to be preserved. However, based on the morphology of the fruit, most of the people of Tegal still have difficulty distinguishing the wirasangka mango from other mangoes. Molecular markers are needed to ascertain the differences between these mango varieties. Microsatellite DNA is a repeating DNA of stable DNA markers with high repeatability and polymorphism. This study analyzes the level of genetic diversity and microsatellite alleles that can differentiate four mangoes from Tegal District, Central Java, Indonesia, i.e. wirasangka, tengkueh, golek, and okyong. Eleven accessions of six locations in Tegal District were analyzed using ten microsatellite loci. The microsatellite amplification result was separated using electrophoresis in 6% polyacrylamide gel and then visualized with silver dye. A total of 35 microsatellite alleles were found measuring 100-1000 bp, ranging from 1-7 alleles for each locus. The average polymorphism information content (PIC) of 0.54 indicates that genetic diversity is relatively high and informative. Therefore, the microsatellite alleles can be used to differentiate mango varieties. The specific allele characteristic of wirasangka mango accession is locus AJ63516, with an allele size of 600-700bp.